THE INSTITUTION “VILLAGE AS A COURT” IN THE CUSTOMARY LAW OF MACEDONIANS - Jelena Cvetanovska (EtnoAntropoZum, 2016)
The institution “village as a court” is a topic that has been rarely and insufficiently taken into consideration in Macedonian ethnology and anthropology up to the present moment. My research is based upon few years of data collection in a number of Macedonian regions, that were then crosschecked with the existing data in the ethnographic literature in the country and the Balkans. Data show that in the Macedonian traditional culture the village acted as a keeper of order and as a judge when it came to the sinful trespassing of norms of the folk law and the moral codex of the community.